Profile of candidiasis in HIV infected patients - P Anwar-Khan; A Malik; H Subhan Khan (Iranian Journal of Microbiology, 2012)
Background and Objective: Candidiasis is a common opportunistic infection in HIV-infected patients. The spectrum of Candida infection is diverse, starting from asymptomatic colonization to pathogenicforms. The low absolute CD4+ T-lymphocyte count has traditionally been cited as the greatest risk factor for the development of Oropharyngeal Candidiasis and current guidelines suggest increased risk once CD4+ T lymphocyte counts fall below 200 cells/μL. Gradual emergence of non-albicans Candida species as a cause of refractory mucosal and invasive Candidiasis, particularly in patients with advanced immunosuppression and problem of resistance to azoles and other antifungal agents in the Candida species is a point of concern. Materials and Methods: A prospective study was carried out over a period of 2 years (2010-2011) on patients suffering from AIDS for the presence of Candida infection. After thorough clinical examination relevant specimens were collected and processed specifically to ascertain Candida infection. Speciation of Candida isolates and antifungal sensitivity testing was also done. The CD4 cell counts of all the patients were estimated and correlated with the presence (or absence) of candidiasis. Results: Out of a total of 165 HIV positive patients, a definitive diagnosis of candidiasis was made in 80 patients. Candida albicans was the most common yeast isolated. Patients with candidiasis had CD4 counts less than 200 cells/mm3. Maximum resistance was seen with fluconazole while no resistance was seen with voriconazole. Conclusion: The most common opportunistic fungal infection in HIV positive patients is candidiasis, affecting the mucocu- taneous system mainly but the invasive form is also common. Resistance to azoles and other antifungal agents in the Candida species is a point of concern.